Early childhood student-teachers’ perspectives on creativity - Michaelidou, Antonia; Pitri, Eliza (Frontiers in Education, 2022)
The changes taking place during the pandemic regarding the interchange between online and face-to-face teaching in the Department of Education of an Eastern Mediterranean private university, led to the need of instructors not only to revisit knowledge on creativity but to examine the views and perceptions of early childhood student-teachers about creativity. More specifically, through informal interviews, we examined 15 junior early childhood student-teachers’ beliefs concerning creativity in general and the traits of a creative individual, whether creativity can be developed in education, and how it could contribute to early childhood teachers’ professional development. In this article, we summarize a qualitative descriptive study that took place in the context of the course Designing Activities in Kindergarten and describe the results from the semi-structured interviews that aimed to find out early childhood student-teachers’ views on creativity providing evidence for the participants’ need for a framework and strategy to guide their creative instructional design and teaching.